EVALUASI USABILITY APLIKASI MICROSOFT WORD MENGGUNAKAN QUESTIONNAIRES NIELSEN'S ATTRIBUTES OF USABILITY (NAU) (STUDI KASUS : MAHASISWA PROGRAM STUDI BIOLOGI UIN SYARIF HIDAYATULLAH JAKARTA TAHUN 2021) - Muhammad Shidqa Irahman; Evy Nurmiati (Indragiri Islamic University, 2023)
Microsoft 365 is a platform that contains a collection of software media (software) that aims to support productivity and assist in accessing information for its users. Microsoft 365 is also cloud-based software and consists of various supporting software that aims to meet the productivity of its users. Microsoft 365 consists of various other Microsoft software such as Microsoft Word, Microsoft Excel, Microsoft Power Point, and so on. One of the software in Microsoft 365 is Microsoft Word. Microsoft Word is usually used by its users to make changes (editing) to a document that contains report text and other digital written documents. Therefore Microsoft Word users must easily understand the use of features in Microsoft Word. In this paper the author will carry out a Usability Evaluation of the use of Microsoft Word using Nielsen's Attributes Of Usability Questionnaires (NAU) as the testing technique. Therefore, in this paper a usability evaluation test is carried out based on 5 categories, namely Learnability, Efficiency, Memorability, Error, and Satisfaction.